FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PENGETAHUAN IBU DALAM PENANGANAN DEMAM PADA ANAK DI PUSKESMAS I KEMBARAN KABUPATEN BANYUMAS - Cahyaningrum, Etika Dewi; Siwi, Adiratna Sekar (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2018)
Fever in children is a condition that often cause anxiety, stress, and phobia for parents. Knowledge of parents about fever must be well controlled by parents, especially mothers. Handling fever is less appropriate can be due to inadequate knowledge so that attitudes and behavior of mothers tend to be excessive. Factors that affect knowledge include education, employment, age, experience, information, and socioeconomic / income. The purpose of this study was to determine factors related to maternal knowledge level in handling fever in children at Community Health Center of Kembaran I of Banyumas in 2018. Methods in this research is corelational analytical research with cross sectional approach. Data collection techniques used primary data obtained from respondents through questionnaires. The sampling technique used incidental sampling with a sample of 60 mothers in Community Health Center of Kembaran I of Banyumas. The result of research showed that there was no correlation between education factor, work, age, and income with mother's knowledge level in fever handling in child, and it was known that there was relationship between experience and information factor with mother's knowledge level in fever handling in child. Keywords: Factors, level of knowledge, handling fever